Numerical Analysis on Chaos Attractors using a Backward Difference Formulation - Rasedee A. F. N.; Abdul Sathar M. H.; Mohd Najib N.; Wong T. J.; Koo L. F. (Lviv Polytechnic National University, 2024)
Indexed by Scopus